ANALYSIS OF THE INFLUENCE OF SALARY AND SUPERVISION ON EMPLOYEE JOB SATISFACTION AT CV MANDIRI SINAR TERANG HAMPARAN PERAK - Adela Yolanda; Sri Rahayu (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This research is entitled "Analysis of the Effect of Salary and Supervision on Employee Job Satisfaction at CV. Mandiri Bright Rays of Silver Expanse.” The sampling technique in this research was using the Arikunto technique so that the sample in this research was 52 respondents. Data collection techniques in this research were carried out by distributing questionnaires, documentation studies and interviews. The types and sources of data used are primary data and secondary data. The data analysis technique in this research uses quantitative data analysis with computer assistance through the SPSS (Statistical Package for Social Science) version 25 program.